THE ROLE OF INDONESIAN LANGUAGE TEACHERS TO FAMILIARIZE THEMSELVES WITH THE POSITIVE CHARACTER AT MI AL-IHSAN MEDARI SLEMAN - Wildan Nuril Ahmad Fauzi; Muqowim (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
The purpose of this research is to know the role of Indonesian teachers in familiarizing the positive character in MI Al-Ihsan Medi. The methods in this study use qualitative with this type of case study. Data and data sources in this study include basic data and supporting data collection techniques in this study, using interviews, observations, and documentation. Data analysis technique with data reduction, data presentation and withdrawal of conclusions (verification). Checking the validity of data using triangulation. The results of the study concluded that the role of Indonesian teachers when familiarizing the behaviour of positive character in the school is, first the teacher domiciled into someone who caused the change. The teaching of a teacher as a figure is being drafted and imitated, because the teacher is a mirror for the development of students ' character education. The two teachers must continue to revive the spirit and ability of the learners. All three teachers are able to unleash the potential of their own learners. The four teachers must be able to teach the learning that contains the character and contain activities on the stage of the deers, reading, writing, and speaking, so that the learners can know the qualities that have themselves.